1035325 Faktor-faktor yang Berhubungan dengan Perilaku Gaya Pacaran Pada Siswa SMK Kesehatan - Selpyani Sinulingga; Susilawati (STIKes Budi Mulia Sriwijaya, 2019)
Abstract Teenagers are children aged 10-24 years which is the age between childhood and adulthood and as a starting point for the reproduction process. In the era of globalization, the social environment is very dynamic which results in changes in adolescent lifestyles including dating behavior. The purpose of this research was to know the factors associated with dating style behavior in Fania Salsabila Health Vocational School students in Jambi City in 2018. The research design used was quantitative with Cross Sectional, the analysis used was Univariate and Bivariate.The results showed that 11.1% of students behaved risky dating, 52.8% had poor knowledge, 44.4% of students were exposed to pornography and 8.3% had peers who had a negative influence. The results showed all variables have been shown to correlate with dating behavior. Based on the results of the research it is advisable for adolescents to increase their knowledge of reproductive health and for the school to increase coaching activities and increase awareness of adolescents with informational activities. Keywords: Teenagers, behavior, datin